Seeking out SDGs in Dialysis Medicine—Selected Articles from the JSDT Conference, Yokohama 2022 (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The theme of the 67th Annual Meeting of the Japanese Society for Dialysis Therapy was "Seeking out SDGs in Dialysis Medicine". SDGs, short for Sustainable Development Goals, encapsulate global objectives for sustainable development. This concept should be put into practice in the field of dialysis medicine, and we believe this Annual Meeting not only identified the essential elements for sustainable goals in dialysis care but also established a clear path towards their realization. In this Special Issue Reprint, we have curated a selection of papers presented during the conference. These papers cover critical topics, such as cardiovascular complications, renal anemia, CKD–MBD, diabetes and nutrition, frailty and sarcopenia, rehabilitation, reactive fibrosis, and environmental concerns. Our hope is that the insights and findings presented in this Special Issue Reprint will bring us significantly closer to the answers we seek.